2008
DOI: 10.2174/1874091x00802010108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the L-arginine-Nitric Oxide Pathway and Oxidative Stress on the Pathogenesis of the Metabolic Syndrome

Abstract: The discovery of the physiological roles of nitric oxide has revolutionized the understanding of regulation of vascular tone, platelet adhesion and aggregation, and immune activation. Perhaps the most intriguing aspect of nitric oxide (NO) is that it is a gas that, in the absence of receptors, can regulate both normal physiological events and mediate cytotoxicity under pathological conditions. NO is produced from L-arginine by NO synthases (NOS), yielding L-citrulline and NO. The regulation of L-arginine pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 93 publications
0
13
0
5
Order By: Relevance
“…The scenario concerning OS and metabolic syndrome (MS) is complex and several studies reported the role of OS in the development of MS [26,27]. In the context of a genetic predisposition to IR induced by excessive caloric intake or sedentary lifestyle, it has been hypothesized a diet-induced OS [28].…”
Section: Discussionmentioning
confidence: 99%
“…The scenario concerning OS and metabolic syndrome (MS) is complex and several studies reported the role of OS in the development of MS [26,27]. In the context of a genetic predisposition to IR induced by excessive caloric intake or sedentary lifestyle, it has been hypothesized a diet-induced OS [28].…”
Section: Discussionmentioning
confidence: 99%
“…The production of O À 2 may contribute to the oxidative inactivation of endotheliumderived NO, by converting it to ONOO À . ONOO À and notably its conjugated peroxynitrous acid are highly unstable in aqueous phase, and they isomerize and decompose to nitrate and nitrite (Assumpçao et al, 2008;Bestermann, 2011;Dayal & Lentz, 2005;Dayal et al, 2004). With regard to these data, endothelium-dependent vasodilatation might be decreased due to decreased bioavailability of NO and levels of NO metabolites might be raised due to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…There is now evidence that insulin modulates the expression of endothelial nitric oxide synthase (eNOS) and stimulates nitric oxide (NO) production, causing vasodilation. On one hand, in the state of insulin resistance, the effects of insulin on eNOS and NO become blunted, resulting endothelial dysfunction (Assumpçao et al, 2008;Johnson et al, 2007;Marchesi et al, 2009). On the other hand, blood homocysteine (Hcy) and asymmetric dimethylarginine (ADMA) levels are markers of endothelial damage and subsequent cardiovascular disorders, and these parameters are linked to other metabolic syndrome symptoms (Bestermann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation and oxidative stress have been implicated in the pathophysiology of Major Depressive Disorder (MDD) (Berk et al, 2011; Capuron and Miller, 2011; Chauhan and Chauhan, 2006; Croonenberghs et al, 2002; Forlenza et al, 2007; Khanzode et al., 2003; Maes, 2011a,b, 1999; Miller, 2010; Raison and Miller, 2011; Wolkowitz et al, 2008) as well as a number of serious medical conditions (Maes et al, 2011b), including cardiovascular disease and atherosclerosis (Krishnan, 2010; Lakshmi et al, 2009; Tousoulis et al, 2008; Uno and Nicholls, 2010), chronic renal disease (Cottone et al, 2008), pulmonary disease (Jelic and Le Jemtel, 2008), rheumatoid arthritis (Stamp et al, 2012), certain cancers (Khansari et al, 2009; Maes et al, 2011b; Reuter et al, 2010), metabolic syndrome, obesity and diabetes (Agrawal et al, 2007; Assumpcao et al, 2008; Ferder et al, 2006; Guerrero-Romero and Rodriguez-Moran, 2006), and in the normal physiology of cellular aging and immuno-senescence (Cannizzo et al, 2011; De la Fuente and Miquel, 2009). While inflammation and oxidation have generally been studied separately in these conditions, the interplay between them has been less well-studied, despite mounting evidence that their interaction plays a major role in the pathogenesis of many diseases (Ambade and Mandrekar, 2012; Forlenza and Miller, 2006; Maes et al, 2011e, 2007; Rahman, 2003; Sarandol et al., 2007a).…”
Section: Introductionmentioning
confidence: 99%